Assuming that x is not 3, simplify: \(\dfrac{8x-4}{x+3} - \dfrac{12x-20}{2x+6}\)

So far I was able to factor the second term: \(\frac{12x-20}{2x+6}=\frac{4(3x-5)}{2(x+3)}=2(3x-5).\)

I plugged 2(3x-5) back into the expression, but I don't know what to do from here. Could I get a hint?

dolphinia Feb 10, 2022

#2**+1 **

Divide the second term by 2/2 to get

[(8x-4) - (6x-10) ] / ( x+3) =

(2x +6) / (x+3)

2 (x+3) / (x+3) = 2

ElectricPavlov Feb 10, 2022

#3**0 **

....and here is an error 4(3x-5)/2(x+3) = 2 (3x-5) / (x+3) ( you dropped the denominator by accident)

ElectricPavlov Feb 10, 2022